The Oppressor’s Matrix: McGill University’s Arab-Israeli Conflict, 1963-1973 - Fried, Jonah Philip (Canadian Jewish Studies / Études juives canadiennes)

(untitled) (Association for Canadian Jewish Studies / Association d’études juives canadiennes, 2025)
After the Israel-Hamas war erupted in October 2023, McGill University in Montreal was one of many North American institutions where students set up encampments in what they described as solidarity with the Palestinian cause. Some have linked this phenomenon to prior student movements, such as those during the Vietnam War or Apartheid in South Africa. But the earliest demonstrations at McGill associated with the Arab-Israeli conflict occurred during Quebec’s Quiet Revolution (1960-1970), a time of significant upheaval in the province. This included unprecedented unrest at McGill: in 1969, ten thousand people marched in “Operation McGill Francais,” a rally that was as much about the French language as it was about anti-colonial revolution. Focusing on this incident, a turning point in Quebec’s anti-imperialist movement, this paper considers the origins of Quebec-Palestine solidarity and analyzes the phenomenon’s impact on McGill–including its Jewish students. Understanding this historical context can shed light on the recent sensitivity of the Israel / Palestine debate at McGill and offer insight into the wider historiography of political tensions on university campuses.